Local Layer Duck Livestock Business Development Strategy In The Desa Pematang Johar Deli Serdang - Akbar Habib; Megawati Siregar (JASc (Journal of Agribusiness Sciences), 2020)
This study aims to determine how much income from the local laying duck business and to find out how the local laying duck business development strategy in Pematang johar village. The research method used is descriptive. Data collection methods by interview, observation, and study documentation. The results showed that the local laying duck business was profitable with an average revenue value greater than the expenditure for a period of Rp. 616,778,235 with an R / C Ratio of 2,039, the strategy of developing local laying ducks usatha using the S-O strategy where the position matrix is in quadrant I (positive, positive) which indicates that the local laying duck business is strong and has a chance. The strategy given is aggressive in which strength is used to seize profitable opportunities.